Practical framework of employability skills for engineering graduate in Malaysia - Zaharim A.; Omar M.Z.; Yusoff Y.M.; Muhamad N.; Mohamed A.; Mustapha R. (2023)
The purpose of this paper is to propose a practical and simple framework of engineering employability skills that will allow the concept to be explained easily and that can be used as a framework for working with engineering graduates to develop their employability before entering workforce. The framework was developed from existing researches on engineering employability skills issues and the requirement of the accreditation of engineering programme. The various skills of employability skills related to engineering included in the framework are discussed and their criteria justified bases on literature review of existing studies. The framework sets out exactly what is meant by engineering employability, in clear and simple terms, and the framework suggests directions for interaction between the various skills. The relationships between the skills within the framework remain theoretical. Further research to test the framework is planned and will be reported in future paper. The framework can be used to explain the concept of employability to those new to the subject, and particularly to engineering students and their future employer. It will be a useful tool for lecturers, careers advisors, trainers, employers and any other practitioners involved in employability skills. It will also be used to develop a model and a measurement tool for engineering employability skills. This paper contributes insights into the linking of graduate attributes, using national accreditation criteria and the framework of engineering employability skills from locally and globally expectation. It will be of value to anybody with an interest in employability issues. 2010 IEEE.